Epidemiological profile of respiratory viruses in pediatrics at HUMAP-UFMS pre and post COVID-19 pandemic (Research, Society and Development, 2024)
Objective: Describe changes in the epidemiological profile of respiratory viruses in pediatrics at HUMAP-UFMS following the COVID-19 pandemic. Method: Retrospective, descriptive cohort study, with analysis of data reported in medical records, referring to pediatric patients (up to 12 years old), of both sexes, admitted to the pediatric emergency room at HUMAP in the period between March 1, 2018 and March 28 February 2023. The data was selected and placed in an Apple Numbers spreadsheet, version 6.0. Categorical variables were expressed as relative (%) and absolute (n) frequencies, arranged descriptively in graphs and tables. JAMOVI2.3.26 statistical software was used. Results: Data from 1326 medical records were analyzed. The most prevalent age group was children under 1 year of age, with a predominance of males. In general, the most common agents were respiratory syncytial virus (RSV) and rhinovirus. ICU admissions were also analyzed and are mainly related to age group. Regarding the period, it was observed that with the reduction of protective measures taken during the pandemic period, in order to prevent the spread of Sars-CoV-2, there was a significant increase in the number of hospitalizations in pediatrics. Conclusion: The results show a higher incidence and severity of respiratory infections in younger children, in all periods analyzed. They also show that with the measures taken during the pandemic there was a change in both the number of hospitalizations and the severity of the conditions presented, reinforcing the need for greater investment in diagnosis, treatment and management in general of pediatric patients with respiratory syndromes.